Monetary policy and banking sector stability in Nigeria - Chizoba E. Didigu; Nsikak J. Joshua; Joel I. Okon; Annette O. Eze; Jurbe Y. Gopar; Charles N. Oraemesi; Blessing-Oxford U. Udofia; Daniel N. Yisa; Jude C. Ejinkonye; Victoria E. Ette (CBN Journal of Applied Statistics, 2022)
This study investigates the impact of monetary policy on banking sector stability in Nigeria, utilizing quarterly data for the period 2007Q1 to 2021Q4. The study employs the autoregressive distributed lag (ARDL) bounds testing approach to coin- tegration. Results show that a long run relationship exist between banking sector stability and monetary policy in Nigeria. Furthermore, monetary policy rate, liquidity ratio, and cash reserve ratio are found to enhance banking sector stability. The study recommends, among others, that cash reserve and liquidity ratios should be kept at levels that will prevent excess liquidity in the system.
Keywords: E44; E52; E58; 330; Banking sector stability; financial system; monetary policy